Fermentation Conditions and Process Optimization of Citric Acid Production by Yeasts - Afolabi, Folake Titilayo; Adeyemo, Stella Mojisola; Balogun, Halimat Osheiza (The International Journal of Biotechnology, 2018)
The aim of this study was to isolate and screen citric acid producing yeasts using low cost substrates. Thirty three yeast isolates were obtained from pineapple, plantain and sugar cane waste and identified as; Saccharomyces cerevisiae, Schizosaccharomyces pombe, Candida tropicalis, Pichia guilliiermondii, Debaromyces sp., Candida parapsilosis, Candida rugosa, and Candida krusei. Candida tropicalis had zone of clearance of 49±2.1 mm in diameter, Pichia guilliermondii had 40±1.2mm. Saccharomyces cerevisiae produced citric acid with glucose with 105.0 mg/l. C. tropicalis yielded 132.2 mg/l with sodium nitrate. S. cerevisiae and C. tropicalis produced citric acid at pH 6 with 23.70mg/l and 23.80mg/l. P. gulliermondii at pH 4 produced 23.00mg/l. The temperature of 30°C favoured S. cerevisiae and C. tropicalis yielding 40.80mg/l and 39.80 mg/l. After extraction, the yield of the citric acid was 4.231g, 3g of which was recrystallized to yield 2.16g of pure citric acid resulting into 72% recovery. The result indicated that pineapple wastes, plantain wastes and sugarcane cane are potential sources of yeasts that can be used for the production of citric acid.